THE GENERIC NAMES PROPOSED FOR HYMENOMYCETES-III * " Clavariaceae" - DONK, M. A. (REINWARDTIA, 1954)
1. This third part deals with "Clavariaceae," a family designation used in a traditional and descriptive, rather than a taxonomic, sanse. 2. Two of the authors previously published proposals for the conservation of certain names are replaced by slightly altered ones. They aim at the safeguarding of the names Clavulinopsis Overeem, Lachnocladium. Lev., and Ramaria (Pr.) Bonord. A proposal to conserve Pterula Fr. in its current sense is withdrawn as superfluous. 3. Some forgotten or neglected names are listed, e.g. Scleroglossum Pers. and Xyloglossum Pers. These two names are typified by a species that makes them synonyms of Acrospermum Tode ex Fr. (Ascomycetes). 4. The following typifications, among others, deserve attention: Dendrocladium Lloyd by Lachnocladium giganteum Pat., Holocoryne (Fr.) Bonord. by Clavaria falcata Pers. ex Fr., and Ramaria S. F. Gray by Clavaria pratensis Pers. 5. One new combination is made: Pistilliva typhae (Hohn.) Donk (basinym, Dacryopsis typhae Hohn.).